Scrutinising The Production Of Space On The Example Of Regent Street and Painting A Modern Life By The Agencies Of Regency - Hidayet Softaoğlu (Journal of Contemporary Urban Affairs, 2019)
The main aim of this is to analyse the production of space and how human and non-human entities function as space producers or devices. The scope of this study is the Regent Street from 1818 to 1848. This paper aims to answer the following question: could space be a product that we can produce or what other things involved in this production process? Numerous theorists contribute to the spatial analyses of this historical research. This paper puts special emphasis on the Lefebvrian spatial triad as a methodological decoder along with the Actor-Network Theory (ANT) to analyse the 19th century-Regent Street. The combination of the triad, as well as the ANT, will be deployed as an original tool to analyse spaces with their data; then they will be used to create a spatial map. To do so, visual and written sources will also be used as data to decode and re-map or re-paint the modern life of Regent Street during the Regency Period.